A Study of Changes in Morphology of Osteoarthritic Articular Cartilage Using Computerized Image Analysis. (23rd April 2013) - Goyal, Neeru; Gupta, Madhur
Abstract : Histological studies on articular cartilage have been traditionally based on individual observations but this approach is limited by its subjectivity and bias, yielding considerable variability. So the present study was conducted to observe the various changes in the morphology of osteoarthritic femoral articular cartilage using computerized image analysis. The cartilage specimens were divided into two groups: group 1 (n = 23 ) (46–81 years) consisted of OA specimens. Group 2 (n = 12 ) (41–86 years) consisted of non-OA specimens. A 5  μ m thick paraffin sections were stained with H&E staining and analyzed using Image-Pro Express image analysis software for quantitative analysis of articular cartilage. Various parameters, namely, total thickness of the cartilage, area of lacunae in each zone, area of subchondral cavities, and number of chondrocytes per 10, 000  μ m 2 area in each zone, were measured. Microscopic appearance of OA cartilage was much different as compared to control. Various changes seen were different in all specimens and they were not related to age. Lacunar size in all four zones was found to differ significantly in the OA (group 1) and control (group 2) (P < 0.05 ). The results suggest that OA should be considered as a specific process and not simply as an inevitable feature of ageing.